Frequency of somatic complains among patients with mental illness - Anum Haider; Usama Asad (Annals of Psychophysiology, 2018)
Background: It is established that physical and mental disorders share common risk factors, among those the unhealthy lifestyle is most common. In order to achieve complete health, it is crucial to monitor both physical and mental health. Mental health problem is the most deserving area to work with because physical health issues are often neglected or mismanaged. This study intends to unveil the frequency of somatic (physical) health complains among patients with mental illness.